Pengaruh Penggunaan Mobile Banking Terhadap Minat Nasabah dalam Bertransaksi pada Bank Muamalat KCP Stabat - Iqbal Raihan; Muhammad Arifin Lubis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research focuses on discussing the influence of the use of mobile banking offered by Bank Muamalat KCP Stabat on the interests of customers who use mobile banking. The aim of this research is to determine the influence of using mobile banking on customer interest and the magnitude of the influence of using mobile banking on customer satisfaction at Bank Muamalat KCP Stabat. This research uses quantitative data and distributes questionnaires. The method used was Non Probability sampling with a sample of 97 respondents. Sampling technique with several criteria and considerations. Meanwhile, the analysis method used is the T test (Partial Test). The results of this research show that the Fcount value is 182.156 > Ftable 3.09 with a significance level of 0.000 < 0.05, so the regression model can be used to predict the influence of the Mobile Banking Use Variable (X) on the Customer Interest Variable (Y). The X regression coefficient of 0.803 states that for every 1% increase in the Mobile Banking Usage value, the Customer Interest value increases by 0.803. The regression coefficient is positive, so it can be said that the direction of influence of variable X on Y is positive.